Morphological Characterization of Papillary Renal Cell Carcinoma Type 1, the Efficiency of Its Surgical Treatment - Procházková, Kristýna; Staehler, Michael; Trávníček, Ivan; Pitra, Tomáš; Eret, Viktor; Ürge, Tomáš; Eberlová, Lada; Roušarová, Milena; Hošek, Petr; Chudáček, Zdeněk; Ferda, Jiří; Hes, Ondřej; et al. (Urologia internationalis, 2017)
AIM: Papillary renal cell carcinoma type 1 (pRCC1) represents the second most common type of malignant renal epithelial tumour. The origin of its characteristic appearance, its growth mechanism, and the long-term efficiency of its surgical treatment remain uncertain. Our aim was to determine typical characteristics of surgically treated pRCC1. METHODS: pRCC1 was verified in 83 of 1,629 (5.1%) kidney tumours surgically treated in the period of January 2007-January 2016. The clinical and radiological characteristics, type of surgery, histopathology results and follow up data were recorded. Spearman correlation, Kruskal-Wallis analysis of variance, Fisher's exact, and chi-square test were used to analyse appropriate variables. The overall survival rate was evaluated using the Gehan-Wilcoxon test and the Cox proportional hazards model. RESULTS: The mean tumour size was 52.0 mm (15-180); 98.8% of the tumours showed a spherical shape and in 82.1%, exophytic growth was observed. Partial nephrectomy was performed in 80.7%. A majority (81.9%) were classified as pT1. Tumours, 89.2% of them, belonged to Fuhrman grade 1 or 2. The mean follow-up was 46.8 months. The overall survival was associated with pT category (p ≤ 0.0001). CONCLUSIONS: Typical signs of pRCC1 are a spherical shape, exophytic growth and low Fuhrman's grade. More than three-fourths of pRCC1 could be treated by the nephron-sparing surgery.
Keywords: výsledek terapie; proporcionální rizikové modely; nádory ledvin; Chi-Square Distribution; Male; retrospektivní studie; Survival Rate; karcinom z renálních buněk; prognóza; Proportional Hazards Models; rozdělení chí kvadrát; Adult; Kidney; Kidney Neoplasms; Aged; dospělí; mužské pohlaví; senioři; nefrektomie; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Humans; ledviny; nefrony; Aged, 80 and over; Prognosis; Carcinoma, Renal Cell; Retrospective Studies; Female; Nephrectomy; Nephrons; lidé středního věku; míra přežití; Middle Aged